2019
DOI: 10.1038/s41598-019-47822-0
|View full text |Cite
|
Sign up to set email alerts
|

ANAC032 regulates root growth through the MYB30 gene regulatory network

Abstract: Reactive oxygen species (ROS) play important roles as root growth regulators. We previously reported a comprehensive transcriptomic atlas, which we named ROS-map, that revealed ROS-responsible genes in Arabidopsis root tips. By using ROS-map, we have characterised an early ROS response key transcription factor, MYB30, as a regulator of root cell elongation under ROS signals. However, there are other ROS-responsible transcription factors which have the potential to regulate root growth. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…4B]; Supplemental Table S9). This finding supports previous findings and suggests that MYB30 has a vast array of overlapping and nonoverlapping functions in cells that may or may not be linked to ROS, HL stress, and/ or SAA (Ogata et al, 1994;Stracke et al, 2001;Yanhui et al, 2006;Li et al, 2009;Dubos et al, 2010;Ambawat et al, 2013;Liao et al, 2017;Mabuchi et al, 2018;Maki et al, 2019). Because light plays such a pivotal role in plants, the triggering of SAA by light stress could impact many different physiological, metabolic, and molecular processes in systemic tissues, and these could be directly or indirectly mediated by MYB30.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…4B]; Supplemental Table S9). This finding supports previous findings and suggests that MYB30 has a vast array of overlapping and nonoverlapping functions in cells that may or may not be linked to ROS, HL stress, and/ or SAA (Ogata et al, 1994;Stracke et al, 2001;Yanhui et al, 2006;Li et al, 2009;Dubos et al, 2010;Ambawat et al, 2013;Liao et al, 2017;Mabuchi et al, 2018;Maki et al, 2019). Because light plays such a pivotal role in plants, the triggering of SAA by light stress could impact many different physiological, metabolic, and molecular processes in systemic tissues, and these could be directly or indirectly mediated by MYB30.…”
Section: Discussionsupporting
confidence: 90%
“…The Arabidopsis (Arabidopsis thaliana) genome contains ;200 genes with a conserved MYB domain, involved in the regulation of a variety of functions, such as growth and development, metabolism, hormone signaling, and responses to biotic and abiotic conditions (Ogata et al, 1994;Stracke et al, 2001;Yanhui et al, 2006;Dubos et al, 2010;Ambawat et al, 2013). Previous studies identified a role for MYB30 in mediating brassinosteroid responses in roots (Li et al, 2009), calcium signaling in response to heat stress (Liao et al, 2017), and root growth and development (Mabuchi et al, 2018;Maki et al, 2019).…”
mentioning
confidence: 99%
“…Therefore, the MYB30 regulatory network activated in response to H 2 O 2 treatment is involved in maintaining the balance between root growth and defense ( Mabuchi et al, 2018 ). In addition, the use of the “ROS-map” revealed another early ROS-responsible transcription factor, ANAC032 , which is NAC [NAM, no apical meristem; ATAF1/2, Arabidopsis transcription activation factor; and CUC2, CUP-shaped cotyledon2 ( Souer et al, 1996 ; Aida et al, 1997 ; Duval et al, 2002 )], as a root growth regulator ( Maki et al, 2019 ). Interestingly, ANAC032 is an upstream transcription factor of the MYB30 regulatory network ( Maki et al, 2019 ).…”
Section: Ros Act As Signaling Molecules For Regulating Root Growthmentioning
confidence: 99%
“…In addition, the use of the “ROS-map” revealed another early ROS-responsible transcription factor, ANAC032 , which is NAC [NAM, no apical meristem; ATAF1/2, Arabidopsis transcription activation factor; and CUC2, CUP-shaped cotyledon2 ( Souer et al, 1996 ; Aida et al, 1997 ; Duval et al, 2002 )], as a root growth regulator ( Maki et al, 2019 ). Interestingly, ANAC032 is an upstream transcription factor of the MYB30 regulatory network ( Maki et al, 2019 ). Previous studies suggested that ANAC032 plays important roles in response to abiotic stresses such as high-intensity light, salinity, and oxidation ( Mahmood et al, 2016 ) and is a key mediator between SA- and jasmonic acid-dependent defense signaling ( Devi Allu et al, 2016 ).…”
Section: Ros Act As Signaling Molecules For Regulating Root Growthmentioning
confidence: 99%
See 1 more Smart Citation